Design and Implementation of a Dual-Band Microstrip Patch Antenna for Wireless Bridging at 2.4 GHz and 5.0 GHz - Salim, Syamila; Kamarudin, Ramlee (Evolution in Electrical and Electronic Engineering, 2026)
This study presents the design and implementation of a compact dual-band microstrip patch antenna incorporating rectangular-shaped and U-slots for wireless bridging at 2.4 GHz and 5.0 GHz. The antenna was designed and simulated using CST Studio software and fabricated on a low-cost FR‑4 substrate with a dielectric relative permittivity constant of 4.3 and a thickness of 1.6 mm, with overall dimensions of 76 x 59 mm2. Simulation results showed resonant frequencies at 2.4 GHz and 5.0 GHz, with return losses of -15.9 dB and -20.5 dB, and bandwidths of 80 MHz and 180 MHz, respectively. The measured results closely matched the simulation, with return losses of -15.9 dB at 2.4 GHz and -10.0 dB at 5.1 GHz. The antenna exhibited directional radiation patterns and low VSWR below 2.0 in both bands. It was applied in a 20-meter point-to-point wireless bridging system using MikroTik L11UG-5HaxD devices, achieving 120 Mbps at the access point and 74 Mbps at the client. Results confirm the antenna’s compact size, efficiency and suitability for reliable Wi‑Fi and short-range wireless bridging.